On the 90th anniversary of the signing of the Lateran Pacts. Their genesis, most important provisions, and significance - Gaca, Andrzej (Studia Iuridica Toruniensia, 2020)
Last year marked the 90th anniversary of the signing of the Lateran Treaties. Their conclusion led to the normalisation of relations between Italy and the Papacy, the creation of the State of the Vatican City, and the conclusion by representatives of the Holy See and the Italian government of a concordat ending nearly sixty years of conflict between the Italian Kingdom and the Church, often referred to as the “Roman question”. Many researchers believe that its origins date back to the events and effects of the French Revolution, with further developments occurring in the first decades of the second half of the 19th century. As early as October 1926, talks were held between lawyers representing the Italian government and the Holy See, with the aim of achieving a positive solution to the problems in question and preparing the conditions for mutual understanding. Such a mutual agreement was reached by virtue of the Acts of 11 February 1929 signed at the Lateran Palace between the Government of the Kingdom of Italy (Benito Mussolini) and the Holy See (Secretary of State Cardinal Pietro Gasparri), known as the Lateran Pacts or Treaties. The result of the Lateran Pacts was the conclusion of three treaties. Under the first one, both parties considered the hostile relationship which had lasted for all those years to be over. Moreover, Pope Pius XI recognized the existence of the Kingdom of Italy with Rome as its capital, and Italy recognised/accepted? the establishment of an independent and fully sovereign Vatican City State under international law. The purpose of the conciliatory convention on financial matters (Convenzione finanziaria) was to regulate the question of compensation to the Holy See for the losses suffered as a result of the On the 90th anniversary of the signing of the Lateran Pacts 71 liquidation of the Church State. An integral part of the Lateran Agreements was also the signing of a concordat, comprising 45 articles, between the Holy See and the Kingdom of Italy.